PEMBENTUKAN DESA LAYAK ANAK DESA BOLO KECAMATAN KARE KABUPATEN MADIUN - Zulin Nurchayati Zulin Nurchayati (Universitas Merdeka Madiun, 2022)
The Village Government controls the existence of natural resources and human resources in the Village. A safe, comfortable and well-cultured environment is the dream of every child in the fulfillment of children's rights. So it is appropriate for the village to provide proper facilities and infrastructure for children's lives. So it is necessary to have a child-friendly village. The expected targets include: 1. The establishment of a child-friendly village can be implemented 2. There is intensive communication between Bolo Village Government officials and the community, 3. There are positive and significant changes to the Village Government regarding a proper environment for children. The methods used in community service are gradual participatory extension and the “PRA” (Participatory Rural Appraisal) approach. The participatory extension method referred to is that the extension worker is actively involved in assisting the community service target group (Village Government Officials and PKK) during the implementation of the service program. Meanwhile, the “PRA (Participatory Rural Appraisal)” approach emphasizes the active involvement of the target group in the formation of child-friendly villages. Meanwhile, the result of community service is a change in positive attitudes, that is, there is public awareness of the environment that is suitable for children.